Clinical and Environmental Reservoirs of Pseudomonas aeruginosa in Rural Tanzania: Implications for Diagnostics and Antimicrobial Stewardship - Philbert Balichene Madoshi; Theresia A. Karuhanga; Sandra Breum Andersen (Urogenital Tract Infection, 2026)
Purpose: Antimicrobial resistance (AMR) is making urinary tract infections (UTIs) and surgical site infections (SSIs) increasingly difficult to treat, especially in low-resource settings where self-medication and limited laboratory services are common. This study explored knowledge and practices related to AMR and investigated Pseudomonas aeruginosa from clinical and environmental reservoirs in Kilombero, rural Tanzania.Materials and Methods: A cross-sectional study was conducted over 9 months at St. Francis Regional Referral Hospital and selected community markets. Questionnaires were used to assess AMR awareness and antibiotic-use practices among community members and healthcare providers. Urine samples from pregnant women, SSI swabs, and fresh fish samples were collected. Fish were included as indicators of environmental reservoirs and possible foodborne exposure to P. aeruginosa. Presumptive isolates were confirmed using polymerase chain reaction targeting the OprI and OprL genes. Antimicrobial susceptibility testing followed EUCAST (European Committee on Antimicrobial Susceptibility Testing) 2021 guidelines.Results: Only 34% of community participants correctly identified bacteria as causes of infection, while 19% had no knowledge of bacterial infections or AMR. Ciprofloxacin was the most commonly used antibiotic (49%), and self-diagnosis was frequently reported (35%), particularly among fish vendors. Poor hygiene practices, including hand-washing without soap, were also common. A total of 271 P. aeruginosa isolates were confirmed. Gentamicin showed the highest effectiveness across all sample sources, while resistance to meropenem and ciprofloxacin was substantial, especially among fish and SSI isolates.Conclusions: Knowledge gaps, self-medication, and inconsistent hygiene coexist with the presence of P. aeruginosa in both clinical samples and fish representing environmental reservoirs Tanzania. Improved diagnostics, antimicrobial stewardship, hygiene practices, and community education are needed to strengthen AMR control using a One Health approach.